PENERAPAN ASESMEN FORMATIF UNTUK MENINGKATKAN LITERASI SAINS PADA MATERI PENCEMARAN LINGKUNGAN - Bella Aprilia, Gita; Wahyu Budi Sabtiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research examines the application of formative assessment to improve science literacy in environmental pollution material at SMPN 11 Surabaya. Science literacy is a crucial competency in the 21st century, yet Indonesian students' performance in PISA 2022 showed only 34% reached basic competency level. This pre-experimental study employed a one-group pretest-posttest design involving 31 seventh-grade students. Formative assessment was integrated into Problem Based Learning through various techniques including student worksheets with feedback columns, peer assessment, self-assessment, and guided reflection. Data were collected through observation sheets, pretest-posttest, and student response questionnaires. Results indicate: (1) learning implementation was excellent at 97.33%; (2) science literacy significantly improved with average N-gain of 0.5 (moderate category), confirmed by Wilcoxon Signed Rank Test (Z = -4.092, Sig. = 0.000); and (3) student responses were very positive at 91.09%. The highest N-gain was achieved in identifying scientific problems (0.71, high category). These findings confirm that systematic formative assessment integration in PBL effectively enhances science literacy in environmental pollution topics. Keywords: formative assessment, science literacy, environmental pollution, Problem Based Learning